Reconstruction of the mechanism of nomination for president and vice president in elections in indonesia - Rahmat Muhajir Nugroho (Universitas Muhammadiyah Magelang, 2022)
The candidacy threshold of President and Vice President in Act Number 7 the Year 2017 concerning Elections causes the Political Party of Elections Participants unable to submit the President and Vice President candidates independently and the recent political parties that participated in 2019 elections. Political Parties have lost their constitutional rights as they cannot propose the candidates of President and Vice President. It is required to find an alternative mechanism of President and Vice President candidacy which grants more protection to the Political Parties' constitutional rights and achieves the essence of people's sovereignty. Article 222 of Act Number 7 the Year 2017 requires the Political Party to have a minimum of 20% seats in the House of Representatives or a minimum of 25% votes of the previous legislative election to submit presidential candidacy. Meanwhile, article 6A section (2) of the 1945 Indonesian Constitution does not govern regarding President and Vice President candidacy; thus, article 222 of Act Number 7 the Year 2017 contradicts the Constitution. The provision in the Elections Act has several implications, among others, limiting the freedom of political parties to submit president candidate, causing discrimination, injustice, and a material loss to the new political party. Moreover, the threshold is not in accordance with the essence of people's sovereignty as granted in the Constitution.